Contrasting behavior of zwitterionic and cationic polymers bound to anionic liposomes - Yaroslavov, A A (Langmuir : the ACS journal of surfaces and colloids, 2007)
Zwitterionic polymers were prepared by quaternizing polyvinylpyridine (DP = 1100) with bromoacids (Br(CH2)nCOOH, where n = 1, 2, 3, and 5). The resulting polymers were then added to unilamellar liposomes composed of egg lecithin or dipalmitoylphosphatidylcholine admixed with 20 mol % of cardiolipin (a phospholipid with two negative charges). These systems were compared (along with polyethylvinylpyridinium chloride, a polycation) by light scattering, electrophoretic mobility, fluorescence, and high-sensitivity differential scanning calorimetry. The external zwitterionic polymers induce no flip-flop of cardiolipin from the inner leaflet to the outer leaflet as does the polycation. Aside from this similarity, the four zwitterionic polymers all behave differently from each other toward the anionic liposomes: (a) For n = 1, there is no detectable interaction between the polymer and the liposomes. (b) For n = 2, electrostatic attraction induces polymer-liposome association (reversed by the addition of NaCl) that maintains the original negative charge on the liposome. Aggregation of the liposomes accompanies polymer adsorption. (c) For n = 3, electrostatic binding also occurs along with aggregation. However, the binding is so strong that NaCl is unable to induce polymer/liposome dissociation. (d) For n = 5, there is polymer binding and NaCl-promoted dissociation but no substantial aggregation. These differences among the closely related polymers are discussed and analyzed in molecular terms